2021
DOI: 10.1007/s10943-021-01328-0
|View full text |Cite
|
Sign up to set email alerts
|

Moral Injury: An Increasingly Recognized and Widespread Syndrome

Abstract: Moral injury (MI), originally discussed in relationship to transgressing moral beliefs and values during wartime among military personnel, has expanded beyond this context to include similar emotions experienced by healthcare professionals, first responders, and others experiencing moral emotions resulting from actions taken or observations made during traumatic events or circumstances. In this article, we review the history, definition, measurement, prevalence, distinctiveness, psychological consequences, man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 80 publications
1
76
2
Order By: Relevance
“… 14 This qualitative study adds additional context to these numbers; the emotions reported—isolation, alienation, betrayal—significantly overlapped with the symptoms of moral injury in military and veteran populations. 28 Some respondents who had expressed these emotions were so distressed to the point where their entire lives had changed dramatically, whereas others who have experienced the same events were disturbed but not as affected in their functioning.…”
Section: Discussionmentioning
confidence: 99%
“… 14 This qualitative study adds additional context to these numbers; the emotions reported—isolation, alienation, betrayal—significantly overlapped with the symptoms of moral injury in military and veteran populations. 28 Some respondents who had expressed these emotions were so distressed to the point where their entire lives had changed dramatically, whereas others who have experienced the same events were disturbed but not as affected in their functioning.…”
Section: Discussionmentioning
confidence: 99%
“…These events are described as potentially morally injurious events (PMIEs), recognizing that not everyone exposed will be impacted in the same way. Evidence from a range of studies in United States (US) military samples suggests that individuals exposed to PMIEs are at greater risk of developing mental health issues, including more severe post-traumatic stress disorder (PTSD), depression, anxiety, and suicidality (summarized in Koenig & Al Zaben, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a surge of interest in MI research in recent years focusing on efforts to understand and frame the construct of MI and the prevalence of MI in diverse populations (e.g., military personnel, veterans, police and other first responders), recently including healthcare workers in the context of the COVID-19 pandemic (Koenig & Al Zaben, 2021 ). The research has been led by mental health-related disciplines (e.g., psychology, psychiatry) as well as spiritual and religious disciplines (e.g., chaplaincy), all of which have played important roles in conceptualizing and developing approaches to address MI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations